1993
DOI: 10.1021/tx00031a016
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of arsenic(III) and arsenic(V) species with glutathione

Abstract: Arsenic is metabolized by living systems using oxidation-reduction and methylation reactions, and reduced glutathione (GSH) has been shown to be important in that metabolism. In this study, the solution reactions between GSH and arsenate, arsenite, and their methylated metabolites, monomethylarsonic acid (MMA) and dimethylarsinic acid (DMA), were characterized using 1H and 13C NMR under a nitrogen atmosphere. Binding to GSH through the thiol group was primarily followed by shifts in the carbon atom bonded to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
267
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(284 citation statements)
references
References 9 publications
16
267
0
1
Order By: Relevance
“…In the presence of reduced GSH, arsenite conjugates with three molecules of glutathione to form ATG. The monomethyl metabolite of arsenic conjugates with two equivalents of glutathione to form methylarsenic diglutathione (MADG) [27,39]. The dimethyl metabolite of arsenic conjugates with one equivalent of glutathione to form dimethylarsenic glutathione (DMAG) [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of reduced GSH, arsenite conjugates with three molecules of glutathione to form ATG. The monomethyl metabolite of arsenic conjugates with two equivalents of glutathione to form methylarsenic diglutathione (MADG) [27,39]. The dimethyl metabolite of arsenic conjugates with one equivalent of glutathione to form dimethylarsenic glutathione (DMAG) [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The monomethyl metabolite of arsenic conjugates with two equivalents of glutathione to form methylarsenic diglutathione (MADG) [27,39]. The dimethyl metabolite of arsenic conjugates with one equivalent of glutathione to form dimethylarsenic glutathione (DMAG) [39,40]. Previous study showed that ATG and MADG, but not DMAG, is transported out of hepatocytes via the MRP2/ cMOAT transporter [27].…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] The sensitivity of tumor cells to As 2 O 3 -induced apoptosis was reported to be inversely related to the intracellular level of glutathione. 23 As shown by Figure 10a, the level of glutathione decreased slightly within the first 3 hr by the treatment with As 2 O 3 .…”
Section: Effects Of As 2 O 3 On Glutathione Content and Superoxide Prmentioning
confidence: 99%
“…Notably, some of these effects could be the consequence of a direct interaction of arsenic trioxide with GSH and protein thiols (Scott et al. 1993; Hughes 2002; Lu et al. 2007; Zhang et al.…”
Section: Introductionmentioning
confidence: 99%